Widespread extrahepatic expression of acute-phase proteins in chicken (Gallus gallus) tissues (International Journal of Health, Animal Science and Food Safety, 2016)
Acute Phase Proteins (APP) are plasma proteins that can modify their expression in response toinflammation caused by tissue injury, infections, immunological disorders, or stress. Although APP areproduced mainly in liver, extrahepatic production has been described (Marques et al., 2016; Lecchi etal., 2012). The aim of this work was to study the extrahepatic gene expression of five APP, namely α1-acid glycoprotein (AGP), Serum amyloid A (SAA), Haptoglobin-like protein (PIT54), C-rective protein(CRP) and Ovotransferrin (OVT) (O'Reilly and Eckersall, 2014) in different healthy chicken (Gallus gallus)tissues by quantitative real time PCR (qPCR) and immunohistochemistry to detect the precise locationof the proteins.APP gene expression was higher in liver compared with other tissues. mRNA coding for CRP, OVT andSAA was detected in all tissues involved in this study with a higher expression in gastrointestinal tract,respiratory system and lymphatic system. SAA expression was particularly high in cecal tonsil, lung,spleen and meckel’s diverticulum, whereas OVT showed a high expression in lung, bursa of Fabricius,pancreas, brain and adipose tissue. AGP and PIT54 was also detected in pericardial adipose tissue,spleen, kidney, lung, mucosa of proventriculus, mucosa of gizzard and pancreas but, oppositely to SAA,their mRNA was not detected in meckel’s diverticulum, cecal tonsil and bursa of Fabricius. These resultssuggest that each tissue is able to express different amount of APP even in healthy conditions andmount a local acute phase reaction. Immunohistochemistry to detect the precise location for AGP, OVTand SAA using available antibodies is ongoing.
Keywords: Acute phase proteins; Animal welfare; Chicken; Gallus gallus